Improving Students' Understanding of Science Concepts: is there a Relationship Between Learning Models and Academic Ability? - Hasnunidah, Neni; Rosidin, Undang; Kadaritna, Nina (FKIP Universitas Lampung, 2024)
The Argument-Driven Inquiry (ADI) learning model, which is considered appropriate for use in higher education, is still not able to overcome students' difficulties in developing argumentative discourse so that their understanding of concepts tends to be low. The management of the learning process for students with different academic abilities requires scaffolding in the ADI model which is implemented gradually from the class, group, and individual levels. This research has produced an Argument-Driven with Scaffolding (ADIS) model which is a modification of the ADI model with the addition of standpoints and phasing. Standpoint as a statement of claim functions in generating arguments through debate. Meanwhile, the phases consisting of initiation, development, and reinforcement function in the development of individual argumentation skills. This study aims to compare the understanding of the concept of students with different academic abilities by using ADI, ADIS, and conventional learning models. The design of a non-equivalent pre-test-post-test control group was used on 180 prospective science teacher students at the University of Lampung. The concept comprehension test is used to measure students' ability to understand the concepts taught from answers in the form of essays. The test questions relate to the level of thinking from Bloom's cognitive domain, namely remembering, understanding, applying, analyzing, evaluating, and creating. The results of the analysis of students' concept understanding data using ANCOVA showed that the achievement of concept understanding with the ADIS learning model was equivalent to ADI but higher than the conventional model. Students with high academic ability have a higher understanding of concepts compared to students with low academic ability. The highest average concept understanding was achieved by students with high academic ability in the ADIS class, while the lowest average was achieved by students with low academic ability in the Conventional class. The ADIS model has been proven to be able to train students' skills in drafting high-quality arguments and participating productively in scientific arguments in stages so as to improve understanding of concepts. Standpoint as a starting point in argumentation development and phasing (initiation, development, and reinforcement) in the ADIS model is effectively used as a scaffolding for students to develop argumentation skills both classically, in groups, and individually. Keywords: academic ability, argument-driven inquiry, conceptual understanding, scaffolding.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1224-1243